Cardio- and Neurotoxicity of Selected Anti-COVID-19 Drugs - Martin W. Nicholson; Ching-Ying Huang; Jyun-Yuan Wang; Chien-Yu Ting; Yu-Che Cheng; Darien Z. H. Chan; Yi-Chan Lee; Ching-Chuan Hsu; Yu-Hung Hsu; Cindy M. C. Chang; Marvin L. Hsieh; Yuan-Yuan Cheng; et al. (MDPI AG, 2022)
Since December 2019, the novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has infected ~435 million people and caused ~6 million related deaths as of March 2022. To combat COVID-19, there have been many attempts to repurpose FDA-approved drugs or revive old drugs. However, many of the current treatment options have been known to cause adverse drug reactions. We employed a population-based drug screening platform using 13 human leukocyte antigen (HLA) homozygous human induced pluripotent cell (iPSC) lines to assess the cardiotoxicity and neurotoxicity of the first line of anti-COVID-19 drugs. We also infected iPSC-derived cells to understand the viral infection of cardiomyocytes and neurons. We found that iPSC-derived cardiomyocytes express the ACE2 receptor which correlated with a higher infection of the SARS-CoV-2 virus (r = 0.86). However, we were unable to detect ACE2 expression in neurons which correlated with a low infection rate. We then assessed the toxicity of anti-COVID-19 drugs and identified two cardiotoxic compounds (remdesivir and arbidol) and four neurotoxic compounds (arbidol, remdesivir, hydroxychloroquine, and chloroquine). These data show that this platform can quickly and easily be employed to further our understanding of cell-specific infection and identify drug toxicity of potential treatment options helping clinicians better decide on treatment options.